The Biblical Paradigm in Postmodern Novelism (Otar Chiladze's novel "everyone that findeth me") - Kutsia, Nana; Todua, Miranda (COLLECTION OF SCIENTIFIC WORKS OF SOKHUMI UNIVERSITY, 2025)
The paper analyzes several enigmas in Otar Chiladze’s novel "Everyone that findeth me", (the sparrow, the tent/tree, the prayer/violet, etc.). Otar Chiladze’s novelistic art continues the centuries-old tradition of Georgian literature – emphasizing enigma-paradigms characteristic of hagiography, even within the epoch of postmodernism. Parallels are drawn with the conceptual passages of The Martyrdom of Abo and The Martyrdom of Shushanik. Georgian postmodernism is replete with biblical enigmas, allusions, and reminiscences. The aforementioned enigma-paradigms are examined and interpreted in parallel with biblical archetypes. Consideration is also given to the commentaries of John of Damascus, John Chrysostom, and Basil the Great on conceptual passages of the Holy Scripture.